2000
DOI: 10.1080/089106000435590
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion to the digestive mucosa is not sufficient for durable persistence of differentLactobacillus fermentumstrains in the digestive tract of mice

Abstract: Adhesion to the digestive mucosa is not sufficient for durable persistence of different Lactobacillus fermentum strains in the digestive tract of mice I. Hautefort To cite this article: I. Hautefort (2000) Adhesion to the digestive mucosa is not sufficient for durable persistence of different Lactobacillusfermentum strains in the digestive tract of mice,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…The remaining isolates failed to produce biofilm using the in vitro model. Our results were in agreement with the previous works, showing an extensive variation in biofilm formation among the isolates [32,27] and supported the notion of no correlation between in vitro attachment and biofilm formation abilities (r=0.11, P=0.51). However, the high ratios of these two abilities were observed only in one isolate, i.e., L. plantarum strain 42.…”
Section: Discussionsupporting
confidence: 93%
“…The remaining isolates failed to produce biofilm using the in vitro model. Our results were in agreement with the previous works, showing an extensive variation in biofilm formation among the isolates [32,27] and supported the notion of no correlation between in vitro attachment and biofilm formation abilities (r=0.11, P=0.51). However, the high ratios of these two abilities were observed only in one isolate, i.e., L. plantarum strain 42.…”
Section: Discussionsupporting
confidence: 93%
“…Our results show that certain strains are able to persist and compete regardless of diet and competing LAB, and, in some cases, competing LAB can fortuitously support persistence of some strains. Hautefort et al (29) found that the presence of a resident microbiota had a positive effect on the adhesion capacity of inoculated strains. The inoculation of, or background presence of, a mixed microbiota may create a synergistic environment that assists some strains in becoming established.…”
Section: Discussionmentioning
confidence: 99%
“…It can be difficult to predict how these in vitro characteristics translate to the corresponding activity in vivo. For example, Hautefort et al (29) reported that several strains were able to persist within mice without adhesion to the GIT lining, indicating that in vitro adhesion assays may be redundant. Gardiner et al (22) argued that performance in the gut can be determined only truly in vivo, suggesting that the time and expense of assays such as those described here may be worthwhile.…”
Section: Discussionmentioning
confidence: 99%
“…This was suggested to be caused by the specificity of attachment site and the removal of mucus (Bezkorovainy 2001). Moreover, Hautefort et al. (2000) also reported that adhesion was not sufficient to ensure the persistence of L. fermentum strains in the digestive tract of mice.…”
Section: Discussionmentioning
confidence: 99%